Prolyl hydroxylase domain 2 protein is a strong prognostic marker in human gastric cancer - Kamphues, Carsten; Wittschieber, Daniel; Weichert, Wilko; Stenzinger, Albrecht (Pathobiology, 2012)
According to recent research, prolyl hydroxylase domain 2 protein (PHD2) plays an important role in human carcinogenesis by inducing neovascularization and tumor growth. The aim of this study was to evaluate PHD2 expression patterns in primary gastric adenocarcinoma and to test for a potential predictive value of PHD2 expression in gastric cancer patients. Methods: In a total of 121 patients, PHD2 expression was investigated by immunohistochemistry in paraffin-embedded tissue and correlated with clinicopathological parameters and patient survival. Results: 64 of 121 gastric carcinomas (52.9%) showed PHD2 expression in tumor cell cytoplasm. In univariate analysis, PHD2-negative patients had a significantly shortened survival in comparison with PHD2-postive patients (19.5 vs. 32.7 months, p = 0.02). Independent prognostic significance could be shown in multivariate analysis for PHD2 expression (p = 0.005), age at diagnosis (p = 0.012), lymph node status (p = 0.016) and R status (p = 0.026). Conclusion: Cytoplasmic PHD2 expression has a strong impact on survival in gastric cancer patients. Therefore, PHD2 represents a useful predictive biomarker in the evaluation of high-risk patients. Furthermore, these results underline the importance of PHD2 in gastric carcinogenesis and may identify PHD2 as a putative target for future gastric cancer therapy.